Dysprosody in Isolated REM Sleep Behavior Disorder with Impaired Olfaction but Intact Nigrostriatal Pathway. Issue 3 (26th November 2021) - Rusz, Jan; Janzen, Annette; Tykalová, Tereza; Novotný, Michal; Zogala, David; Timmermann, Lars; Růžička, Evžen; Šonka, Karel; Dušek, Petr; Oertel, Wolfgang
Abstract: Background: Impairments of olfactory and speech function are likely early prodromal symptoms of α‐synucleinopathy. Objective: The aim of this study is to assess whether dysprosody is present in isolated rapid eye movement sleep behavior disorder (iRBD) with hyposmia/anosmia and a normal nigrostriatal system. Methods: Pitch variability during speech was investigated in 17 iRBD subjects with normal olfactory function (iRBD‐NOF), 30 iRBD subjects with abnormal olfactory function (iRBD‐AOF), and 50 healthy controls. iRBD subjects were evaluated using the University of Pennsylvania Smell Identification Test and [123I]‐2ß‐carbomethoxy‐3ß‐(4‐iodophenyl)‐ N ‐(3‐fluoropropyl)‐nortropane dopamine transporter single‐photon emission computed tomography (DAT‐SPECT). All iRBD subjects completed the 24‐month follow‐up with DAT‐SPECT, speech, and olfactory testing. Results: At baseline, only iRBD‐AOF showed monopitch when compared to iRBD‐NOF ( P = 0.04) and controls ( P = 0.03), with no difference between iRBD‐NOF and controls ( P = 1). At follow‐up, dysprosody progressed only in iRBD‐AOF with abnormal DAT‐SPECT ( P = 0.03). Conclusion: Prosody is impaired in hyposmic but not in normosmic iRBD subjects before the nigrostriatal dopaminergic transmission is affected (Braak stage 2). © 2021 International Parkinson and Movement Disorder Society